Pemodelan fasilitas pejalan kaki di pusat pertokoan (Studi Kasus di Pusat Pertokoan Salatiga) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT The developinent of shopping areas existing in many cities in Java often puts less attention on the high intensity circulation of vehicles and pedestrians. The curb or sidewalk of roads existing in shopping areas is not necessarily designed to accommodate high value of pedestrian traffic. Inadequate planning and design result in congested traffic, pedestrian-traffic conflict, high incident of accidents and uncomfortable walking environment. This research emphasizes on the development of model for pedestrian facilities provision in shopping areas. The work covers prediction on effective width and height of sidewalk, and areas in the corners of a street intersection. The study area is in the city centre of Salatiga at Sudirman street. Investigations embrace pedestrian flow, state of pedestrian facilities, size of the shopping area, vehicle circulation and parking. The use of video played a significant role in data collection and analysis.